MAQASHID SYARI’AH DAN HAK ASASI MANUSIA (IMPLEMENTASI HAM DALAM PEMIKIRAN ISLAM) - Kasdi, Abdurrahman (LP2M IAIN kUDUS, 2014)
MAQASHID SYARI’AH AND HUMAN RIGHTS (IMPLEMENTATION OF HUMAN RIGHTS IN ISLAMIC THOUGHT). This research intends analysed relationship between ‘maqashid shari’ah’ and human rights in the context of Islamic thought. In some text and context of Islamic civilization, Islam respects equality. Islam gives freedom, both thinking and doing. Humans have a sense that is used to assess and see the surroundings. God gives the freedom of expression, criticizing and rectifying the country steps. Related to human rights, human being is a central point that gets attention. All the concepts and theory directed towards how to maintain mankind virtue. In the classification stage, these rights can be grouped into the most important, important and less important. To provide a solution to the phenomenon, the most ideal is to use a ‘maqashid’ concept that is implemented with ‘fiqh aulawiyat’ (priority). To promote and realize the ‘maqashid’ concept, it requires skillful people. Incorporating the concept of Islamic human rights in the International level becomes an indicator of the implementation of these two relations.keywords: ‘Maqashid Syari’ah’, Human Right, ‘Dlaruriyah’, ‘Hajjiyah’, ‘Tahsiniyah’Penelitan ini bermaksud mengkasji relasi antara maqashid syari’ah dan hak asasi manusia dalam konteks pemikiran Islam. Dalam beberapa teks dan konteks peradaban Islam, Islam sangat menghormati persamaan hak. Dalam masalah kebebasan; baik berfikir maupun berbuat, Islam memberikan keluasaan selebar–selebarnya. Manusia memiliki akal yang dipergunakan untuk menilai dan melihat alam sekitarnya. Allah memberikan kebebasan mengutarakan pendapat, mengkritik dan meluruskan langkah–langkah negara. Dalam perbincangan tentang HAM, manusia adalah titik sentral yang mendapatkan perhatian. Semua konsep dan teori diarahkan bagaimana untuk menjaga kemashlahatan umat manusia. Dalam tahap klasifikasi, hak–hak tersebut bisa dikelompokkan menjadi paling penting, penting dan kurang penting. Untuk memberikan solusi atas fenomena tersebut yang paling ideal adalah dengan memakai konsep maqashid yang diimplementasikan dengan fiqh aulawiyat (prioritas). Untuk mengedepankan konsep maqashid ini diperlukan tangan–tangan terampil sehingga bisa terealisir. Memasukkan konsep HAM Islam dalam tingkat International, menjadi indikator implementasi dua relasi ini.kata kunci: Maqashid Syari’ah, HAM, Dlaruriyah, Hajjiyah, Tahsiniyah